Akuammiline alkaloid derivatives: divergent synthesis and effect on the proliferation of rheumatoid arthritis fibroblast-like synoviocytes - Bao, Xinye; Wei, Jian; Tao, Cheng; Bashir, Muhammad Adnan; Zhang, Hai-Jun; Bao, Bian; Chen, Jian; Zhai, Hongbin (Frontiers in Chemistry, 2023)
Natural products remain to be the important source of medicines to treat various major diseases such as rheumatoid arthritis (RA), given their excellent biocompatibility and structural diversity. Herein, we have developed a versatile synthetic method for constructing various skeletons of akuammiline alkaloid analogues based upon our previous research on the total synthesis of the related indole alkaloids. We have also evaluated the effect of these analogues on the proliferation of RA fibroblast-like synoviocytes (FLSs) in vitro and analyzed the corresponding structure-reactivity relationship (SAR). Among these analogues, compounds 9 and 17c have demonstrated promising inhibitory effect on the proliferation of RA-FLSs, with IC50 value of 3.22 ± 0.29 μM and 3.21 ± 0.31 μM, respectively. Our findings provide a solid foundation for future pharmacological studies on akuammiline alkaloid derivatives and aspiration for the development of anti-RA small molecule drugs derived from natural products.